Long-range influence of steps on water adsorption on clean and D-covered Pt surfaces. Issue 13 (30th September 2014) - den Dunnen, Angela; van der Niet, Maria J. T. C.; Badan, Cansin; Koper, Marc T. M.; Juurlink, Ludo B. F.
Abstract : Water wets the D-covered Pt(111) surface (right), while it clusters at steps of D-covered Pt(533), (755), and (977) (left). Abstract : We have examined water desorption from Pt(111) terraces of varying width and its dependence on precoverage by deuterium (D) with temperature programmed desorption studies. We observe distinct water desorption from (100) steps and (111) terraces, with steps providing adsorption sites with a higher binding energy than terraces. Preadsorption of D at the steps causes annihilation of water stabilization at the steps, while it also causes an initial stabilization of water on the (111) terraces. When the (111) terraces also become precovered with D, this water stabilization trend reverses on all surfaces. Destabilization continues for stepped surfaces containing up to 8-atom wide (111) terraces with a (100) step type and these become hydrophobic, in contrast to surfaces with a (110) step type and with the infinite (111) terrace. Our results illustrate how surface defects and a delicate balance between intermolecular forces and the adsorption energy govern hydrophobic vs. hydrophilic behavior, and that the influence of steps on the adsorption of water on nano-structured platinum surfaces has a very long-ranged character.